Growth and yield of direct-seeded basmati rice under different ICM modules - Das, Kajal; Pooniya, Vijay; Choudhary, Anil K.; Bana, R.S.; Parihar, C.M.; Sarkar, Susheel Kumar; Swarnalakshmi, K.; Singh, Arjun (Annals of Agricultural Research, 2019)
A field experiment was conducted during Kharif season of 2016, to study the plant height, dry matter accumulation at different growth stages and grain yield of direct-seeded basmati rice under different integrated crop management (ICM) modules. The experiment was laid out in a randomized block design with three replications and eight treatment combinations i.e., ICM modules (ICM1 to ICM8). The study revealed that the plant height, dry matter accumulation at different growth stages and grain yield (4.03 t ha–1) of direct-seeded basmati rice under different ICM modules were statistically and numerically higher in the ICM7 i.e., zero till (ZT)-summer mungbean residue retention (SMB-RR) + ZT- direct seeded rice (DSR) + wheat residue @ 3 t ha–1 + 75% of recommended dose of fertilizers @ 100:50:50 N: P2O5: K2O kg ha–1 (RDF) (N through Zn coated urea/ZCU) + glyphosate as pre-plant (PP) @ 1 kg a.i. ha–1 + pretilachlor as pre-emergence (PE) @ 0.75 kg a.i. ha–1 followed by bispyribac-sodium @ 25 g a.i. ha–1 as post emergence (POE) at 25 days after sowing (DAS) + need based water management, disease and integrated pest management, with comparison to other modules. Direct seeding of rice in ICM7 module increased grain yield by 4.13, 9.51 and 19.9% over direct seeding/transplanting under ICM8 (ZT-SMB-RR + ZT- DSR + wheat residue @ 3 t ha–1 + 50% RDF + AMF + NPK-biofertilizers (liquid formulation) + glyphosate as PP @ 1 kg a.i. ha–1 + pretilachlor- PE @ 0.75 kg a.i. ha–1 fb bispyribac-sodium @ 25 g a.i. ha–1 as POE at 25 DAS + 1 HW), ICM1 (Conventional transplanting/TPR + 100% of RDF + butachlor-PE @ 1 kg a.i./ha + 1 HW) and ICM2 (TPR + 75% RDF (N as ZCU) + NPK- biofertilizers + butachlor as PE @ 1 kg a.i. ha–1 + 1 HW) modules. This study suggests that zero-tilled direct-seeded rice in wheat and summer mungbean residue retained plots (ICM7) with adoption of suitable weed management practices produced comparable yields as in transplanted rice (ICM1).